The theoretical impact of the listing of syariah-approved stocks on stock price and trading volume. - Carl B. , McGowan Jr; Muhammad, Junaina (Clute Institute, 2010)
The stock price and trading volume reactions of companies to single events, such as public announcements on mergers, dividend payments, or security issue announcements have been studied extensively. The impact of news about a continuing event such as the news on the inclusion in and exclusion of stocks from the KLSE Syariah Index that occurs twice yearly affects security prices and trading volume. This paper examines reasons that price and trading volume of Syariah-approved stocks might react to the inclusion-exclusion exercise. The selection criteria set by the Syariah Advisory Council of Securities Commission of Malaysia in updating the list of the Syariah-approved stocks is not based on the financial soundness alone. Views from Syariah perspective and from financial theories are discussed to support the behavior of the included and excluded stocks from the Kuala Lumpur Syariah Index.